3(x+4) is the same as 3x+12 when the brackets are expanded out
You simply multiply the expression on the outside (in this case, 3) by each of the expressions inside the parentheses, and add everything up. In this case, 3x + 3 times 4.
The sum of 3x plus 2 and -4 plus 3 is 3x+1 if the equation is (3x+2)+(-4+3). If they are two separate questions, 3x+2 remains as itself while -4+3=-1.
-3x+14 = -4 -3x = -4-14 -3x = -18 x = 6
4 + 8x
3x + 4 = 16 3x = 16 - 4 x = 12/3 x = 4
You simply multiply the expression on the outside (in this case, 3) by each of the expressions inside the parentheses, and add everything up. In this case, 3x + 3 times 4.
3(x plus 3) expanded --> 3x+9
6x + 8
(3x+4)(x-2) 3x2 -6x+4x-8 3x2-2x-8
It is: 3x+4
The answer is y = -3x -4.
The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.
38*4 + 3 + 7 - 3x = 162 - 3x
6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...
The sum of 3x plus 2 and -4 plus 3 is 3x+1 if the equation is (3x+2)+(-4+3). If they are two separate questions, 3x+2 remains as itself while -4+3=-1.
3x+56 = 2x+4 3x-2x = 4-56 x = -52
9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2